Anthropometrical Characteristics and Somatotype of Young Macedonian Soccer Players - Gontarev, Seryozha; Kalac, Ruzdija; Zivkovic, Vujica; Ameti, Vullnet; Redjepi, Agim (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2016)
The success in sport performance is closely related to the physical condition of the sportsman. In the assessment of the physical status except physiological and fitness parameters, significant influence have the anthropometric parameters. The aim of the study was dual: to assess the changes in the anthropometric characteristics and the somatotype of young soccer players at different ages and to compare these characteristics with the general population. The analyzed measurements of 486 young soccer players who play in teams of the First national league, with an average age 15.8±1.4. The soccer players were divided into five subgroups, at age difference of 1 year. In the sample height, weight, BMI index, diameters, volumes and skin folds were measured, also the body composition and the somatotype were calculated. Boys from 14 years were lower and had less tendencies of other age groups. From 16 years onwards there were no differences in the measurements which means that the respondents gradually get the look of adult players. All skin folds for young Macedonian players (except the skin folds of the scapula) decrease with age and compared to the peers from normal population are lower. For young players in all age groups dominate the mesomorphic component, and lower values have the endomorphic component, in regards to peers in the general population. The obtained results can serve as normative anthropometric indicators for regular sports medical examinations of young players in our country, or can be used as a template for comparison of the anthropometric and somatotype information of young players at a similar level of different countries.
Keywords: Soccer; Young; Anthropometry; Somatotype; Growth; Age.